Riesgo de resultados obstétricos y perinatales adversos en cordón nucal, de gestantes del Hospital Regional de Loreto, julio 2021 - julio 2022 - Cárdenas Golac, Rodrigo Javier (2023)
Objectives: To analyze the risk of adverse obstetric and perinatal events, in the presence of nuchal cord, in patients who gave birth at the Regional Hospital of Loreto from July 2021 to July 2022. Methods: Observational, analytical, case-control design. Cases were represented by the presence of circular nuchal cord and controls without the presence of nuchal cord. Results: There were 130 cases and 130 controls. Age older than 25 years predominated, with 50.8% (66/130) in cases and 51.5% (67/130) in controls. Gestational age at term predominated in both groups with 63.8% (83/130) of the cases and 54.6% (54.6%) of the controls. Hemoglobin was normal more frequently in both groups. Of the total, 32.3% (84/260) had a cesarean section with the presence of a circular cord, as opposed to 17.6% (46/260) who had a vaginal delivery. There was no statistical significance between the obstetric and perinatal events. The preterm infant had a 4.3 times greater risk of presenting circular nuchal cord (OR: 4.3; 95% CI: 1.59-11.56), there was a greater risk with increased length of the nuchal cord (OR: 1.05; 95% CI: 1.028-1.086; p=0.000) and gestational age (OR: 0.795; 95% CI: 0.654-0.967; p=0.022). Conclusions: Within obstetric events, the size of the circular cord, and within perinatal events, the preterm ones, influence as risk factors for the presence of circular nuchal cord.